Guy Bourdin : in between (Göttingen : Steidl, 2010)
Guy Bourdin's vivid, narrative-infused work placed him at the vanguard of fashion photography for a career that spanned four decades. 'In Between' delves into that career, charting the course of his artistic development from the 1950s to the 1980s.
boek
Keywords: Bourdin, Guy